Combined annotation‐dependent depletion score for BRCA1/2 variants in patients with breast and/or ovarian cancer. Issue 2 (17th January 2018) - Nakagomi, Hiroshi; Mochizuki, Hitoshi; Inoue, Masayuki; Hirotsu, Yosuke; Amemiya, Kenji; Sakamoto, Ikuko; Nakagomi, Satoko; Kubota, Takeo; Omata, Masao
Abstract : Utility of combined annotation‐dependent depletion (CADD) score was recently reported to rank pathogenicity as C‐scores ranging 1‐99 for both confirmed deleterious mutation. Using C‐scores for BRCA1/2 variants, we tried to constitute the classification system for variant of uncertain significance (VUS), which had been a major problem of genetic testing for hereditary breast and/or ovarian cancer. We analyzed BRCA1/2 genes for 283 patients with breast and/or ovarian cancer. The deleterious mutation and missesne mutations, minor variant, and wild type of BRCA1 and ‐ 2 were 5, 27, 251 and 15, 85, 183, respectively. Meanwhile, the variants with C‐score ≥10 were involved in 19/283 (6.7%) in BRCA1 and 34/283 (12%) in BRCA2 . All deleterious mutations were included in this group. Frequency of personal history and family history of ovarian cancer were significantly high, and frequency of serous adenocarcinoma of ovary and triple negative breast cancer was relatively high in the group with deleterious mutations. Similar findings were seen in patients with variants of C‐score ≥10. According to the C‐score and population frequency, we could define VUS for 11 patients out of 283 patients (3.9 CADD is useful to classify the variant of BRCA1/2 and selecting the patient who needs further segregation studies. Abstract : Combined annotation‐dependent depletion (CADD) score is useful to classify BRCA1/2 variants in patients with breast and/or ovarian cancer.